KEPEMIMPINAN KEPALA SEKOLAH BERBASIS NILAI KEARIFAN LOKAL TORAJA “TALLU BAKAA” (STUDI MULTI-SITUS PADA SMAN 3 DAN SMAN 5 KABUPATEN TANA TORAJA) - Somakila, Resty Sari; Ansar; Muh. Ardiansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research examines the principal's leadership based on the Toraja local wisdom value, “Tallu Bakaa,” at SMAN 3 and SMAN 5 Tana Toraja. The background of this study is the shift of local cultural values due to globalization and the lack of research on the implementation of Tallu Bakaa value in school leadership. The purpose of this study is to describe how Tallu Bakaa value-based leadership is implemented and to identify factors that support and hinder its implementation. The methodology used was a qualitative approach with a multi-site case study design. Data collection techniques included in-depth interviews, passive participation observation, and documentation study. The results showed that Tallu Bakaa leadership is implemented through the cultivation of four main values: kinaa (noble character, wisdom, and religious observance), manarang (intellectual and emotional intelligence), barani (courage to make correct and responsible decisions), and sugi' (success as a result of the other three values). This implementation is manifested in exemplary leadership, discipline enforcement, and 3S (Smile, Greet, Greet) acculturation. The main supporting factors are the leadership competence of the principal, the synergy of the school community, and the culture of discipline. Meanwhile, the inhibiting factors are the uneven understanding of the value of Tallu Bakaa among the school community, the habituation process that takes time, and inadequate school facilities.